2009
DOI: 10.1090/s0002-9947-09-04872-7
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic-like maximal operators on integrable functions and Bellman functions related to Kolmogorov’s inequality

Abstract: Abstract. For each q < 1 we precisely evaluate the main Bellman functions associated with the behavior of dyadic maximal operators on R n on integrable functions. Actually we do that in the more general setting of tree-like maximal operators. These are related to and refine the corresponding Kolmogorov inequality, which we show is actually sharp. For this we use the effective linearization introduced by the first author in 2005 for such maximal operators on an adequate set of functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 12 publications
0
35
0
Order By: Relevance
“…See e.g. [4,5,6,7,8,13,14] and the monograph [3], consult also references therein. The primary goal of the present paper is to establish a sharp weighted version of (1.2).…”
Section: Introductionmentioning
confidence: 99%
“…See e.g. [4,5,6,7,8,13,14] and the monograph [3], consult also references therein. The primary goal of the present paper is to establish a sharp weighted version of (1.2).…”
Section: Introductionmentioning
confidence: 99%
“…In fact it has been shown that This has been proved in a much more general setting of tree like maximal operators on non-atomic probability spaces. The result turns out to be independent of the choice of the measure space.The study of these operators has been continued in [7] where the Bellman functions of them in the case p < 1 have been computed. As in [5] and [7] we will follow the moregeneral approach.…”
Section: Introductionmentioning
confidence: 99%
“…The result turns out to be independent of the choice of the measure space.The study of these operators has been continued in [7] where the Bellman functions of them in the case p < 1 have been computed. As in [5] and [7] we will follow the moregeneral approach. So for a tree T on a non atomic probability measure space (X, µ), we define the associated dyadic maximal operator, namely…”
Section: Introductionmentioning
confidence: 99%
“…Such functions related to inequality (1.3) are precisely evaluated [1,2]. Actually if we define for any p > 1 (1.4) where Q is a fixed dyadic cube, φ is non-negative in L p (Q ) and F , f satisfy 0 f F 1/p .…”
Section: Introductionmentioning
confidence: 99%